Apley's concise system of orthopaedics and fractures - Solomon, Louis; Warwick, David 1962-; Nayagam, Selvadurai (CRC Press/Taylor & Francis Group, 2014)
Apley and Solomon's Concise System of Orthopaedics and Trauma is firmly established as the leading introductory textbook of orthopaedic practice and the principles of fracture management. Praised in previous editions for its systematic approach, balanced content and easy-to-read style, the fourth edition has been brought fully up to date with more than 800 illustrations, many new to this edition, providing an invaluable pictorial account of this highly visual subject.